1993
DOI: 10.1242/dev.118.4.1279
|View full text |Cite
|
Sign up to set email alerts
|

Sperm require β-N-acetylglucosaminidase to penetrate through the egg zona pellucida

Abstract: Fertilization in the mouse is initiated by sperm beta 1,4-galactosyltransferase (GalTase) binding to terminal N-acetylglucosamine residues on the zona pellucida glycoprotein ZP3. Binding of ZP3 induces exocytosis of the sperm acrosome, whose contents are believed to digest a penetration slit in the zona matrix through which sperm reach the egg. As a consequence of acrosomal exocytosis, GalTase is redistributed to the lateral aspect of the sperm head, where its function remains unknown. In this location, GalTas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Each glycoprotein contains glycans covalently linked to asparagine (N-linked) and/or serine and threonine (O-linked) . Previous studies indicated that the adhesion of sperm to the egg is mainly mediated by a specific interaction of sperm surface molecules with the glycan moieties on the ZP. Glycosidase digestion and mass spectrometric analyses have indicated that several mouse ZP3 terminal monosaccharide residues, including β- N -acetylgalactosamine (GalNAc), β- N -acetylglucosamine (GlcNAc), mannose, galactose, and sialyl, may be critical for sperm binding to the ZP. Although a fucosylated glycan was identified on human ZP and the addition of a fucose residue to the GlcNAc and galactose trisaccharides enhances mouse sperm–egg binding affinity, the participation of fucose in mouse gamete binding is not definitive.…”
mentioning
confidence: 99%
“…Each glycoprotein contains glycans covalently linked to asparagine (N-linked) and/or serine and threonine (O-linked) . Previous studies indicated that the adhesion of sperm to the egg is mainly mediated by a specific interaction of sperm surface molecules with the glycan moieties on the ZP. Glycosidase digestion and mass spectrometric analyses have indicated that several mouse ZP3 terminal monosaccharide residues, including β- N -acetylgalactosamine (GalNAc), β- N -acetylglucosamine (GlcNAc), mannose, galactose, and sialyl, may be critical for sperm binding to the ZP. Although a fucosylated glycan was identified on human ZP and the addition of a fucose residue to the GlcNAc and galactose trisaccharides enhances mouse sperm–egg binding affinity, the participation of fucose in mouse gamete binding is not definitive.…”
mentioning
confidence: 99%
“…Enzymes observed in semen might play several roles; for example, AcP in mammals takes part in the conversion of proacrosin to acrosin [20], β-NAGase is associated with the acrosome, and its inhibition in mouse sperm results in a lower percentage of fertilised eggs [21]. Our earlier experiment revealed that the AcP present in ide and sturgeon sperm might have an active role in egg fertilisation [8,9], but we also observed no effect of ammonium molybdate addition during carp fertilisation (Sarosiek, unpublished data).…”
Section: Effect Of Inhibitors On Enzymatic Activities Sperm Motility ...mentioning
confidence: 99%
“…It has been previously established that PUGNAc 2 is a potent competitive inhibitor of both O-GlcNAcase 3,26 and bhexosaminidase. 18, 25 For the human enzymes the respective K I values are 46 nM and 36 nM. 3, 21 As described above, selective inhibitors of these enzymes are of interest and we therefore evaluated the selectivity of putative inhibitors 16a-f.…”
Section: Inhibition Studiesmentioning
confidence: 99%
“…O-(2-Acetamido-2-deoxy-D-glucopyranosylidene)amino Nphenylcarbamate (PUGNAc) 18,28 2 is another compound that suffers from the same problem of lack of selectivity, yet has enjoyed use as an inhibitor of both human O-GlcNAcase 3, 26 and the family 20 human b-hexosaminidases. 25 This molecule, developed by Vasella and coworkers, was found to be a potent competitive inhibitor of the b-N-acetyl-glucosaminidases from Canavalia ensiformis, Mucor rouxii, and the b-hexosaminidase from bovine kidney. 18 One rationale for the potency of PUGNAc 2 toward both the family 84 O-GlcNAcases and the family 20 b-hexosaminidases is the sp 2 hybridisation of the anomeric carbon.…”
Section: Introductionmentioning
confidence: 99%